2019
DOI: 10.1111/resp.13615
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric and adult bronchiectasis: Specific management with coexisting asthma, COPD, rheumatological disease and inflammatory bowel disease

Abstract: Bronchiectasis, conventionally defined as irreversible dilatation of the bronchial tree, is generally suspected on a clinical basis and confirmed by means of chest high-resolution computed tomography. Clinical manifestations, including chronic productive cough and endobronchial suppuration with persistent chest infection and inflammation, may deeply affect quality of life, both in children/adolescents and adults. Despite many cases being idiopathic or post-infectious, a number of specific aetiologies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 97 publications
0
14
0
1
Order By: Relevance
“…Bronchiectasis is one of the most common respiratory disorders in IBD patients; its frequency ranges from 18% to 26% and it may precede or follow disease diagnosis. 15 , 16 In our cohort three IBD patients had bronchiectasis (3%), and there were two CD patients and one UC patient. Exacerbations are usually caused by acute bacterial infections, 17 , 18 thus, the importance of vaccinations regimen adherence cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 78%
“…Bronchiectasis is one of the most common respiratory disorders in IBD patients; its frequency ranges from 18% to 26% and it may precede or follow disease diagnosis. 15 , 16 In our cohort three IBD patients had bronchiectasis (3%), and there were two CD patients and one UC patient. Exacerbations are usually caused by acute bacterial infections, 17 , 18 thus, the importance of vaccinations regimen adherence cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 78%
“…At the clinical level, our findings highlight the importance of sputum surveillance for all patients with COPD with bronchiectasis; at the research level, we advocate for better evidence on the effectiveness of eradication or long-term suppressive therapy for potentially pathogenic microorganism or non-tuberculosis mycobacteria infection. 57 Our meta-analysis showed that subjects with COPD and with bronchiectasis had different demographic characteristics, clinical manifestations, and also laboratory parameters, and that these factors were individually associated with prognosis. Therefore, early diagnosis and management of bronchiectasis is of major importance for the prognosis of patients with COPD.…”
Section: Study or Subgroupmentioning
confidence: 75%
“…The pathogenesis of pulmonary involvement in IBD is not well understood. Molecular mimicry or aberrant cell homing from the shared embryological origin of the pulmonary and intestinal system from the primitive foregut may play a role in the disease process [ 30 ]. Colonic and respiratory epithelia express submucosal lymphoid tissue and are important for host mucosal defence mechanisms.…”
Section: Pathophysiologymentioning
confidence: 99%